„Urban Citizenship" und räumliche Aushandlungsprozesse zwischen türkischen Migranten und syrischen Flüchtlingen - Koca, Burcu Togral (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
This article critically discusses how Turkish migrants as an established migrant group have interpreted and acted on the arrival of Syrian refugees in Berlin from 2015 onwards and whether their responses have resulted in new spaces in which new contestations and/or solidarities emerge. To this end, it focuses on the processes and the ways in which established groups (re-)articulate their urban citizenship and belonging to a particular urban space in relation to newcomers. Building on the analytical framework of relational and agency-centered articulation of urban citizenship and drawing on research data collected in the Kreuzberg and Neukölln neighborhoods of Berlin, the analysis has two main findings. Firstly, Turkish migrants have been involved in solidarity activities and contribute to a more inclusive urban citizenship regarding Syrian refugees. At the same time, they perceive Syrian refugees as a threat to their standing in the city and their right to the usage of urban space. This results in a more defensive urban citizenship against the refugees. Secondly, the unequal power relations and local, national and transitional dynamics act as intervening factors shaping Turkish migrants' responses to Syrian refugees and the process of urban citizenship formation.
Keywords: Berlin; urban citizenship; Turkish migrants; Syrian refugees; spatial encounter